A Systematic Review of the Comparison of Three Medicinal Licorices, Based on Differences of the Types and Contents about Their Bioactive Components. Issue 1 (2018) - Zhang, Yong-Jiao; Yang, Yong-An; Gong, Hai-Bin; Zhu, Hai-Liang
No abstract available